International experience of legal regulation of nuclear energy use and its development in other countries - Kukeyev, A.K. (Bulletin of the Karaganda University “Law Series”, 2025)
This article provides an overview of the global experience in legal regulation in the field of nuclear energy. It focuses on the evolution of legislative approaches in leading foreign countries, analyzing both international legal initiatives and national legislation. The article also considers modern challenges related to nuclear safety, liability, and the development of new technologies aimed at environmental sustainability. The purpose of the study is to analyze various approaches to legal regulation of the nuclear industry, assess the effectiveness of current mechanisms, and identify key trends and principles that contribute to safe and sustainable nuclear energy development at the national and international levels. This forms the basis for recommendations on developing a national regulatory framework based on best international practices and the recommendations of the IAEA. Additionally, we can identify ways to harmonize national legislation with international standards and obligations. The methodological foundation is a comparative analysis of legal institutions, norms, and approaches to nuclear energy regulation in various countries. Through the comparative legal method, the study highlights differences in legislative systems, regulations, and enforcement practices among leading nuclear states. This also allows us to identify common trends and effective regulatory models. As a result, the study identifies key features of global experience in legal regulation of nuclear energy use and outlines main trends in its development abroad. Foreign experience provides us with valuable lessons and examples that can be effectively applied in our national legal framework to ensure the safe, sustainable, and socially acceptable use of nuclear energy.